Pengaruh Komunikasi Interpersonal, Gaya Kepemimpinan, Budaya Organisasi Terhadap Kinerja Guru Di MAN 2 Model Medan - Riduan Pohan (Ability: Journal of Education and Social Analysis, 2021)
There is still a lack of communication and openness between principals and teachers in MAN 2 Medan Model. Principals rarely participate in activities at school. There is a gap between teachers and school principals. The lack of communication attitude of the principal causes the organizational culture to be less good so that groupings are formed between teachers. Principals should work closely with teachers. Through interpersonal communication the principal can embrace the teacher as a whole. So that a good organizational culture will be created in the school environment. Research objectives: determine the effect of interpersonal communication on teacher performance, determine the effect of leadership style on teacher performance, determine the influence of organizational culture on teacher performance, and determine the effect of interpersonal communication, leadership style, organizational culture on teacher performance. The research was conducted at MAN 2 Jalan Williem Iskandar No. 7a Medan in November 2020. This research is a quantitative study, with the same population and sample, namely 68 people, using the Totally Sampling method. There is a positive and significant influence of interpersonal communication on teacher performance. by 18.8%. There is a positive and significant influence of organizational culture on teacher performance by 25.7%. There is a positive and significant influence of leadership style on teacher performance by 32.1%. There is a positive and significant influence between interpersonal communication, organizational culture, leadership style together on teacher performance by 41.2%.